GROWTH HORMONE LEVEL EVOLUTION IN CHILDREN WITH HEPATOBILIARY DISEASES, UNDERGOING LIVER TRANSPLANTATION - O. P. Shevchenko; O. M. Tsirulnikova; Y. E. Lourie; A. V. Bougrov; I. E. Tsirulnikova; D. G. Akhaladze; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2012)
End stage liver disease is often associated with growth retardation in children with congenital and hereditary diseases of hepatobiliary system. The aim was to investigate the serum growth hormone level before and after liver transplantation in 52 children with congenital and hereditary diseases of hepatobiliary system. Data of our research work revealed increased serum level of growth hormone in children with liver cirrhosis (3,32 ± 7,7 ng/ml vs. 1,16 ± 1,46 ng/ml in healthy children, p = 0,01), which correlates with PELD score (r = 0,62, p < 0,001). In a month after liver transplantation growth hormone concentration decreases (p < 0,001) and in a year after transplantation it doesn’t differ from healthy children. There wasn’t revealed any interaction between serum growth hormone level and anthropometric parameters before liver transplantation, but in a year after there was significant correlation between growth hormone concentration and height (r = 0,79, p = 0,01). Investigation of growth hormone level in children with liver cirrhosis and its evolution after liver transplantation is of interest as objective criterion of recovery of physical development regulation and as an additional parameter, which cor- relates with severity of end-stage liver disease.